Acoustic wave based MEMS devices, development and application - Voiculescu, Ioana; Nordin, Anis Nurashikin (InTech, 2012)
Acoustic waves based MEMS devices offer a promising technology platform for a wide range of applications due to their high sensitivity and the capability to operate wirelessly. These devices utilize acoustic waves propagating through or on the surface of a piezoelectric material. An acoustic wave device typically consists of two layers, metal transducers on top of piezoelectric substrate or thin films. The piezoelectric material has inherent capabilities of generating acoustic waves related to the input electrical sinusoidal signals placed on the transducers. Using this characteristic, different transducer designs can be placed on top of the piezoelectric material to create acoustic wave based filters, resonators or sensors.